STRATEGIC MANAGEMENT ACCOUNTING AND COMPETITIVE ADVANTAGE: A SCOPUS BIBLIOMETRIC ANALYSIS - Aulia, Amira; Soenaria, Syaiful; Tanzil, Nanny (JRAK, 2026)
This study addresses the limited understanding of the intellectual structure and evolution of research on strategic management accounting (SMA) and competitive advantage. The study aims at mapping key themes and emerging directions in this field. Using a bibliometric approach, 159 Scopus-indexed documents were analyzed through co-word and thematic mapping techniques. The findings show increased publication growth after 2018 and reveal a dual structure: a traditional core focused on cost and competition, and an emerging stream linking SMA to decision-making and performance. The study implies that SMA is evolving as an information capability, while AI, supply chain, and sustainability remain promising research areas.